Towards Person-Centered Quality Care for Children with Life-Limiting and Life Threatening Illness: Self-Reported Symptoms, Concerns and Priority Outcomes from a Multi-Country Qualitative Study - Namisango, Eve; Bristowe, Katherine; Mwangi-Powell, Faith N.; Higginson, Irene J.; Harding, Richard (Palliative Medicine, 2020)
Paediatric life-limiting and life-threatening conditions (life-limiting conditions) place significant strain on children, families and health systems. Given high service use among this population, it is essential that care addresses their main symptoms and concerns.This study aimed to identify the symptoms, concerns and other outcomes that matter to children with life-limiting conditions and their families in sub-Saharan Africa.Cross-sectional qualitative study in Kenya, Namibia, South Africa and Uganda. Children/caregivers of children aged 0–17 years with life-limiting conditions were purposively sampled by age, sex and diagnosis. Children aged 7 and above self-reported; caregiver proxies reported for children below 7 and those aged 7 and above unable to self-report.A total of 120 interviews were conducted with children with life-limiting conditions (n = 61; age range: 7–17 years), and where self-report was not possible, caregivers (n = 59) of children (age range: 0–17) were included. Conditions included advanced HIV (22%), cancer (19%), heart disease (16%) endocrine, blood and immune disorders (13%), neurological conditions (12%), sickle cell anaemia (10%) and renal disease (8%). Outcomes identified included physical concerns – pain and symptom distress; psycho-social concerns – family and social relationships, ability to engage with age-appropriate activities (e.g. play, school attendance); existential concerns – worry about death, and loss of ambitions; health care quality – child- and adolescent-friendly services. Priority psycho-social concerns and health service factors varied by age.This study bridges an important knowledge gap regarding symptoms, concerns and outcomes that matter to children living with life-limiting conditions and their families and informs service development and evaluation.
Keywords: Symptoms, concerns, outcomes, children, palliative care, paediatrics